Global, regional, and national burden of self-harm among adolescents aged 10-24 years from 1990 to 2021, temporal trends, health inequities and projection to 2041 - Tan, Jiang; Shu, Yanping; Li, Qing; Liang, Lifan; Zhang, Yu; Zhang, Jiyuan; Wu, Gang; Luo, Yu (Frontiers in Psychiatry, 2025)
BackgroundSelf-harm ranks as the third leading cause of disability-adjusted life years (DALYs) among adolescents globally, imposing substantial disease and economic burdens. Comprehensive analyses of global temporal trends, health inequities, and future projections are crucial for developing effective public health policies and interventions.MethodsThis study analyzed the global, regional, and national age-standardized incidence, mortality, and DALYs for self-harm among adolescents using data from the Global Burden of Disease (GBD) 2021 database. Significant disease burdens and temporal trends were assessed. Projections and evaluations employed a combination of health inequities analysis, age-period-cohort (APC) analysis, socio-demographic index (SDI) analysis, Joinpoint regression analysis, and Bayesian APC modeling.ResultsThe global burden of self-harm among adolescents demonstrated an overall downward trend. However, in 2021, the burden increased with age and is projected to decline further by 2041. Joinpoint regression analysis revealed a generally decreasing temporal trend, although some regions exhibited stable or slightly increasing trends. Significant regional and national heterogeneities were identified. The High SDI region showed a slight upward trend in incidence, Southern Latin America experienced the largest increase, and the Middle SDI region showed the largest decrease. Conversely, East Asia demonstrated the most significant reductions in both incidence and mortality. Age effects were most pronounced in Low-middle SDI regions, while period and cohort effects exhibited greater fluctuations in High SDI regions. Notably, SDI analysis revealed a positive, fluctuating nonlinear relationship with age-standardized DALYs (r = 0.324, P < 0.001). Gender and regional disparities were also significant. Male adolescents in Middle and High SDI regions bore a higher burden of mortality, whereas female adolescents in Low SDI regions experienced a disproportionately high incidence. Adolescents aged 15-24 carried the greatest burden, with females exhibiting a higher incidence and males experiencing higher mortality rates.ConclusionDespite an overall decline, significant gender and regional disparities persist. Male adolescents in higher SDI regions and females in lower SDI regions are particularly vulnerable. These findings underscore the need for targeted interventions addressing gender and regional inequalities, optimizing healthcare resource allocation, improving health education, and reducing the socioeconomic costs associated with self-harm in adolescents.